Strategi “Public Relations” dalam Promosi Pariwisata: Studi Kasus dengan Pendekatan “Marketing Public Relations” di Provinsi Banten - Chatamallah, Maman (FIkom Unisba, 2008)
Management and promotion about tourims are very important to influence tourist in order to visit and stay in the destination of area of tourism. the Banten departement of tourism are important to use the approach of marketing public relations in order to develop product tourism and public cooperation to make promotion tourism.